English Prospective Teachers' Views on Using Poetry to Enhance Reading Skills - Ni Komang Arie Suwastini; Luh Putu Karina Febriyanti Aryawan; Lulu April Farida (Universitas Hamzanwadi, 2023)
Exploring the role of poetry in language education, this study seeks to understand its impact on reading skills from the perspective of EFL students preparing to become English teachers. With the increasing globalization of English, the techniques for teaching and enhancing its comprehension are evolving. Poetry, with its rhythmic and metaphorical nuances, offers a unique avenue to tap into this development. Using a descriptive qualitative approach, the research engaged ninety-one English Language Education program participants. The findings reveal multifaceted benefits: a significant majority viewed poetry as an avenue for vocabulary enhancement, emphasizing its rich and varied lexicon. Others associated poetry with improvements in literal comprehension, attributing this to the layered meanings often found in poems. The attributes of critical thinking, interpretation of figurative language, grammar refinement, and reading fluency were also highlighted, reflecting poetry's comprehensive influence on reading dimensions. These insights underscore the pedagogical value of poetry in language development, suggesting that integrating authentic poetic materials not only enriches the language repertoire but also amplifies the depth and relevance of the learning experience for students.